A simple data structure for 3D GIS modelling - Boguslawski, Pawel (2012)
ISG brings together scientist from academia, industry and government to analyze progress and to explore new research directions. It focuses on emerging topics and basic research findings across all sectors of geoinformation technologies. The conference program aims to attract leading geoinformation researchers from all fields to reflect the interdisciplinary breadth of geoinformation, including cognitive science, computer science, engineering, geography, information science, mathematics, philosophy, psychology and social science. ISG offer an exciting technical program, including plenary session, technical sessions and in-depth workshops. The symposium is designed to meet scientific, technical and business needs of the geoinformation community testing.